Sistemas de cultivos de milho consorciado ou não com plantas de cobertura de solo: Aspectos produtivos, socioeconomicos e de qualidade - Dalla Chieza, Emerson (2010)
The availability of small areas for cultivation together with the technical and economic deficiencies often aggravated by socio-cultural aspects, creating the small farms, a scenario likely to farming practices with a high degree of unsustainability. From this contest was held this field study, between September 2008 and October 2009 an agrarian reform settlement aimed at examining different forms of soil management, its potential for improving soil quality and its implications for socioeconomic in small farms. The experimental design was randomized blocks with split plots with four replications. The treatments consisted of plots of crop systems: maize + cowpea (M + FC), maize + Pigeon pea dwarf (M + GA); corn + velvet bean (M + MP) and maize monocrop (MS). The sub-plots by the forms of fertilizer: organic source - turkey litter (AO); Without the addition of nutrients (SA) and mineral source - NPK (AM). We assessed aspects related to grain yield of corn, physical and chemical properties of soil in two layers (0-5 and 5-10 cm depth) and socioeconomic aspects of managements. Water stress led to a negative effect of M + FC on grain yield of maize, which in turn was not affected by M + MP, and were higher in treatments with AM (P <0.05). Cultures GA and MP had the highest intakes of nitrogen (N) via aboveground. The cropping systems showed positive results for bulk density and soil porosity. There was a tendency to decrease in aggregate stability for all systems studied, including the fallow treatment. There was no increase (P <0.05) of soil organic carbon (COT) of the systems studied, only attenuated the decrease of this natural element. Showed an increase (P> 0.05) compared to the initial content of N in the soil, and the consortium M + MP which showed the highest levels in both studied layers. The study also found decreased (P <0.05) in the attributes SMP pH, base saturation, exchangeable potassium content, reflecting the increase (P <0.05) in aluminum saturation. Another aspect observed was the increase (P <0.05) CTCpH7.em both layers. The systems studied showed net negative reflections of the high cost of some inputs and low yields obtained. The demand for labor by the managements of the systems has been affected by sowing cover crops for soil, and the management of these, either by restricting the growth of vegetation or the harvest of the seeds. Although it was short time for consistent evaluations, the results obtained by cropping systems indicate that there are gains in productive aspects, contribution of COT and N, especially in soil physical properties. This condition reflects the possibility of replacing the "conventional" system of cultivation of maize by the systems studied, with gains in sustainability, in many ways.